2019
DOI: 10.1007/s11469-019-00128-8
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative Characteristics of Marginalised Novel Psychoactive Users: a Transnational Study

Abstract: New psychoactive substances (NPS) continue to be considered as a major public health concern in many European countries. The study was implemented within the framework of a transnational project of six European countries (Germany, Hungary, Ireland, Netherlands, Poland, Portugal). Our aim here is to report on the distinct and differentiating characteristics of marginalised NPS users. Three subgroups of a total of 3023 adult NPS users (socially marginalised, night life, online community) were examined regarding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
3
1
1
Order By: Relevance
“…These results are consistent with those obtained in other studies conducted in Poland, where it was shown that the legality or assessment of addictive properties does not matter for the majority of users [22]. However, our results, differ from the findings from other countries, e.g., studies of Barratt et al [20] and Soussan and Kjellgren [21,27], where the alleged legality, price, and high availability of the NSP were presented as important motives for the substance use.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are consistent with those obtained in other studies conducted in Poland, where it was shown that the legality or assessment of addictive properties does not matter for the majority of users [22]. However, our results, differ from the findings from other countries, e.g., studies of Barratt et al [20] and Soussan and Kjellgren [21,27], where the alleged legality, price, and high availability of the NSP were presented as important motives for the substance use.…”
Section: Discussionsupporting
confidence: 90%
“…The research by Soussan and Kjellgren [21,27] shows that the desire to feel pleasure is one of the most common motives for using new psychoactive substances. We obtained similar results in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, following the control of many SCRA compounds as class B substances under the MDA or under the PSA, SCRA use in the general population was observed to decline (Blackman and Bradley, 2017). However, significant prevalence in some vulnerable sub-groups remains, particularly homeless individuals and those imprisoned who continue to use SCRAs due to their accessibility and difficulty in analytical detection (Blackman and Bradley, 2017;Brunt et al, 2017;Felvinczi et al, 2020;Ford and Berg, 2018;Norman et al, 2020;Peacock et al, 2019;Scourfield et al, 2019;Weinstein et al, 2017). Indeed, a major driver for SCRA use is their lack of odour during consumption, and lack of appearance on standard drug screens -factors that are well documented in the use of cannabis itself (Gray et al, 2021).…”
Section: Skewed By Scrasmentioning
confidence: 99%
“…Another group of users consists of people who—often because of their criminal past or in an addiction care context—are subjected to regular drug testing and use NPS due to their poor detectability [ 7 ]. NPS users also increasingly include people engaged in highly problematic drug use, often experiencing homelessness, for whom the high potency and relatively low price of these substances are usually the decisive factors for use [ 5 – 7 , 10 , 11 ]. On top of this, a growing number of people use NPS unintentionally.…”
Section: Introductionmentioning
confidence: 99%